ANALISIS TEKNIS DAN EKONOMIS PRODUKSI ARANG AKTIF INDUSTRI PEDESAAN - Tjutju Nurhayati; Saepuloh Saepuloh; Sylviani Sylviani (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
The objectives of this trial was to produce activated charcoal from 5 raw material species which are abundantly potential. The production was conducted in an experimentally designed kiln, expectedly appropriate as a manufacturing prototype of activated charcoal for the inherent endeavors or small-scale village industries, which would be feasible technically, economically, and environmentally. The parameters related to the technical analysis covered the manufacture of charcoal from three wood species (bakau, mangium, and tusam) and coconut shell; analysis on raw material for such charcoal and on the mixed charcoal from the market; activation process using water vapor and air at consecutively 0.25 bar and 4-5 atmospheric pressures, with the temperature as high as 705-805°C; and analysis on iod number for the quality of activated charcoal. For economic evaluation, the inherent parameters covered production cost, activated charcoal price, and other related aspects. For the comparative assessments were used activated charcoals from sawdust and coconut shell from industry. The results are as follows:The yields of resulting activated charcoal were varying, i.e 77% from mangrove charcoal as the highest, followed in decreasing order at 73% from coconut shell charcoal, 66% from both mangium and mixed charcoal, until 58% from tusam charcoal as the lowest. lod number of activated charcoal ranged between 472-722 mg/g, with the one from coconut shell charcoal as the highest and the mangrove charcoal as the lowest. The increase of iod number in coconut shell activated charcoal was the highest with six times higher in comparison to the one in its regular charcoal, followed in decreasing order by those mixed charcoal, tusam charcoal. until mangrove charcoal as well as mangium charcoal as the lowest ( i.e consecutively 3.98 times, 3.39 times and 2.45 limes).Compared to the Indonesian requirement standard for activated charcoal, such production trial of activated charcoal seemed to be insatis factory. This is caused by overall iod numbers which were still below 750 mg/g. However, the iod number in activated charcoal from coconut shell in this trial was still higher than the one in the corresponding activated charcoal produced commercial industries (i.e 722 mg/g). Meanwhile, the iod number in activated charcoal from mixed charcoal (654 mg/g) was lower, but still higher than those from tusam and mangium.The retort for the production trial activated charcoal was constructed of stainless steel reactor with 120 liter volumetric capacity and capable of producing 10 kg per day, using regular charcoal as raw material and firewood as a fuel. This retort was designed as a prototype model for the production of activated charcoal for small-scale industries. The method of production expectedly will not bring about enviromental impacts, since the generated vapour/gas during the activation was immediately incinerated in the fuelwood fire pol.The analysis revealed that the production using coconut shell charcoal as raw material in the retort with design capacity of 250 kg per month and 5 years technical life could be sold at Rp 6,000.- per kg of activated charcoal and therefore could bring in some net benefit at 5.5%. Activated charcoal production using mixed wood charcoal did not give significant any benefit. The benefit of activated charcoal production using coconut shell in that period would be even higher.